Determinants of Sociodemographic and Health Information Factors on the Decision to Undergo Pap Smear among Women of Reproductive Age in Pulau Harapan - Dwi Nurmawaty; Rini Handayani; Muniroh Muniroh (Sean Institute, 2026)
Cervical cancer was the fourth most common cancer among women worldwide in 2022, with an estimated 604,000 new cases and 342,000 deaths. In Indonesia, according to the 2018 Basic Health Research (Riskesdas), cervical cancer ranks second after breast cancer, with an incidence of approximately 23 cases per 100,000 population and a mortality rate of 17 per 100,000 population. This study employed a quantitative approach with a cross-sectional design. The population consisted of 561 women of reproductive age residing in Pulau Harapan Village. The sample size was determined using a two-proportion test, resulting in 150 respondents. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis included univariate and bivariate analyses using the Chi-square test. The majority of respondents were aged 30–39 years, married, had higher education, were unemployed or housewives, and had a monthly income of less than IDR 3,000,000. Most respondents reported easy access to healthcare facilities and received information and education about cervical cancer from healthcare professionals. Sociodemographic factors significantly associated with Pap smear utilization were age (p = 0.000) and marital status (p = 0.000). Meanwhile, the health information factor significantly associated with Pap smear utilization was the source of health information (p = 0.040). These findings indicate that improving Pap smear utilization in island communities requires strengthening community-based health education strategies and optimizing the role of healthcare professionals as primary sources of health information. It is recommended that community health centers and local governments intensify active promotion, expand periodic mass screening programs, and integrate Pap smear education into routine health services to increase early cervical cancer detection among women of reproductive age.